Menakar Pencatatan Perkawinan di Indonesia Perspektif Kaidah Fiqhiyyah: Antara Legalitas Negara dan Keabsahan Syariah - Rahmad Setyawan (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research examines marriage registration in Indonesia through the lens of fiqhiyyah principles, exploring its role in determining marriage validity. Using a descriptive-analytical approach, this library-based study draws data from various sources, including books, journals, scholarly works, the Qur'an, hadith, dictionaries, encyclopedias, laws, court decisions, and other available documents. The findings reveal two primary perspectives on marriage registration: one views it as a non-essential administrative step that serves merely as evidence of marriage, while the other sees it as an additional requirement for marriage validity. Despite these differing opinions, fiqhiyyah principles emphasize that marriage registration, although not a determinant of validity, is a legal obligation that all Indonesians must observe. This requirement is grounded in the principles of promoting welfare and preventing harm. Thus, marriage registration serves as a means to support these goals, ensuring that state legality and sharia validity align to fulfill the objectives of marriage.